2020
DOI: 10.1002/sim.8828
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of three‐arm parallel cluster randomized trials with small numbers of clusters

Abstract: In this article, we review and evaluate a number of methods used in the design and analysis of small three‐arm parallel cluster randomized trials. We conduct a simulation‐based study to evaluate restricted randomization methods including covariate‐constrained randomization and a novel method for matched‐group cluster randomization. We also evaluate the appropriate modelling of the data and small sample inferential methods for a variety of treatment effects relevant to three‐arm trials. Our results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…With more than two arms, Ciolino et al 19 proposed a class of P ‐value based balance metrics, and concluded that Kruskal‐Wallis test P ‐value with a threshold (P>0.3) leads to acceptable balance. Watson et al 8 extended the l2 balance metric in Raab and Butcher 11 for multi‐arm cRCTs as the sum of the cluster‐level standardized mean differences across all arms, and followed Li et al 18 to choose the lowest 10% of the randomization space (in terms of the balance score) for constrained randomization. In the current study, we wish to control the maximum degree of the between‐arm imbalance and therefore propose an alternative extension of the l2 metric of Raab and Butcher 11 .…”
Section: Constrained Randomization In Multi‐arm Crctsmentioning
confidence: 99%
See 3 more Smart Citations
“…With more than two arms, Ciolino et al 19 proposed a class of P ‐value based balance metrics, and concluded that Kruskal‐Wallis test P ‐value with a threshold (P>0.3) leads to acceptable balance. Watson et al 8 extended the l2 balance metric in Raab and Butcher 11 for multi‐arm cRCTs as the sum of the cluster‐level standardized mean differences across all arms, and followed Li et al 18 to choose the lowest 10% of the randomization space (in terms of the balance score) for constrained randomization. In the current study, we wish to control the maximum degree of the between‐arm imbalance and therefore propose an alternative extension of the l2 metric of Raab and Butcher 11 .…”
Section: Constrained Randomization In Multi‐arm Crctsmentioning
confidence: 99%
“…In addition, because there is little prior discussion on how to carry out randomization‐based inference in multi‐arm cRCTs, and given randomization‐based inference could be naturally coupled with constrained randomization, 17,18 we develop most‐powerful randomization tests in Section 3.2, extending the approach of Braun and Feng 26 to multiple arms and additional null hypotheses. Our evaluation assumes a cross‐sectional design with only a single post‐treatment outcome observation for each individual in each cluster, which resembles the TESTsmART study and represents the scenario where constrained randomization provides the maximum benefit for covariate balance 8 . We do not evaluate repeated cross‐sectional or cohort designs, but note that the horizontal before‐after comparisons in these alternative designs already offer some protection against between‐cluster imbalance.…”
Section: Statistical Inference Under Constrained Randomization In Mul...mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies found that increasing cluster size variability led to decreasing power [32][33][34][35], and that the magnitude of the power loss depended on the value of the ICC [33,36]. Eldridge et al [17] concluded that if the cluster size CV is less than 0.23, there is no need to account for the effects of variable cluster size in the sample size calculation.…”
Section: Design Considerationsmentioning
confidence: 99%